Avaliação da densidade de um Planossolo submetido a diferentes sistemas de cultivo ao longo do tempo através da Tomografia Computadorizada. - Bamberg, Adilson Luís (2007)
The agricultural sustainability of the rice (Oryza sativa L.) cultivation in lowland soils is based on the use of different cultivation systems and cultures, needed for a more efficient red and black rice control. The effects of these systems on the soil attributes, mainly in the long run, deserve deeper studies, particularly compaction. The present work had the objective of evaluating the bulk density of an Albaqualf submitted to different cultivation systems, in 19 years of a long-term experiment, through the use of the Volumetric Ring and the Computerized Tomography Methods, and compared the results obtained with that obtained from Pedrotti (1996) at 10 years of the experiment conduction. The experiment has been conducted since 1985, in the Lowland Experimental Field of the Embrapa Clima Temperado, in a random box plot with 8 treatments and 4 replications. It was concluded that the Computerized Tomography Method allowed the identification of a soil surface sealing (0,005 a 0,02m), mainly in the T1 (one year rice with conventional tillage followed by two years of fallow), T4 (rice x soybeans (Glicine Max L.) rotation under conventional tillage), T5 (soybeans x corn (Zea maiz L.) x rice rotation under conventional tillage), and T7 (soybeans under conventional tillage x rice under no-tillage rotation), and other in the 0,08 to 0,14m layer (plow pan), in the T1, T2 (continuous rice under conventional tillage), T4 and T5 treatments, in comparison to the control treatment (T8), that was not detected by the Volumetric Ring Method. In the 0,04 to 0,08m layer, in the other hand, all treatments presented bulk density values significantly lower or similar to the control treatment, with the opposite situation in the 0,12 to 0,18m layer, except to the T6 treatment (rye-grass (Lolium multiflorum L.) and rice under no-tillage succession). The T5 treatment showed higher bulk density values along the entire studied layer (0- 0,20m), while the T6 treatment showed values closer to the control treatment. The bulk density values obtained after 19 years of the experiment conduction where systematically lower than those obtained by Pedrotti (1996) at 10 years of conduction in the same experiment.